Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Decreases in frequency-dependent intrinsic activity of the default mode network are associated with depression and cognition in patients with postacute sequelae of SARS-CoV-2 infection - Yao Wang; Ziwei Yang; Xiumei Zheng; Xiao Liang; Lin Wu; Chengsi Wu; Jiankun Dai; Yuan Cao; Xianjun Zeng; Meng Li; Fuqing Zhou (Brain Structure and Function, 2025)

Topological functional network analysis of cortical blood flow in hyperacute ischemic rats - Bochao Niu; Hongzhou Wu; Yilu Li; Benjamin Klugah-Brown; George Hanna; Youwang Yao; Junlin Jing; Talha Imtiaz Baig; Yang Xia; Dezhong Yao; Bharat Biswal (Brain Structure and Function, 2024)

Mapping sagittal-plane reference brain atlas of the cynomolgus macaque (Macaca fascicularis) based on consecutive cytoarchitectonic images - Yue Luo; Xiangning Li; Can Zhou; Guangcai Liu; Xueyan Jia; Xiaoquan Yang; Anan Li; Hui Gong; Zhao Feng (Brain Structure and Function, 2024)

Using modular connectome-based predictive modeling to reveal brain-behavior relationships of individual differences in working memory - Huayi Yang; Junjun Zhang; Zhenlan Jin; Pouya Bashivan; Ling Li (Brain Structure and Function, 2023)

The Notch pathway regulates autophagy after hypoxic–ischemic injury and affects synaptic plasticity - Kexin Li; Meng Lu; Mengxu Cui; Xiaoming Wang; Yang Zheng (Brain Structure and Function, 2023)

A comparative study of the superior longitudinal fasciculus subdivisions between neonates and young adults - Wenjia Liang; Qiaowen Yu; Wenjun Wang; Thijs Dhollander; Emmanuel Suluba; Zhuoran Li; Feifei Xu; Yang Hu; Yuchun Tang; Shuwei Liu (Brain Structure and Function, 2022)
The superior longitudinal fasciculus (SLF) is a complex associative tract comprising three distinct subdivisions in the frontoparietal cortex, each of which has its own anatomical connectivity and functional roles. However, many studies on white matter development, hampered by limitations of data quality and tractography methods, treated the SLF as a single entity. The exact anatomical trajectory and developmental status of each sub-bundle of the human SLF in neonates remain poorly understood. Here, we compared the morphological and microstructural characteristics of each branch of the SLF at two ages using diffusion MRI data from 40 healthy neonates and 40 adults. A multi-shell multi-tissue constrained spherical deconvolution (MSMT-CSD) algorithm was used to ensure the successful separation of the three SLF branches (SLF I, SLF II and SLF III). Then, between-group differences in the diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) metrics were investigated in all the SLF branches. Meanwhile, Mahalanobis distances based on all the diffusion metrics were computed to quantify the maturation of neonatal SLF branches, considering the adult brain as the reference. The SLF branches, excluding SLF II, had similar fibre morphology and connectivity between the neonatal and adult groups. The Mahalanobis distance values further supported the notion of heterogeneous maturation among SLF branches. The greatest Mahalanobis distance was observed in SLF II, possibly indicating that it was the least mature. Our findings provide a new anatomical basis for the early diagnosis and treatment of diseases caused by abnormal neonatal SLF development.

The impact of Alzheimer's disease susceptibility loci on lateral ventricular surface morphology in older adults - Shan Li; Na An; Nan Chen; Yin Wang; Lin Yang; Yalin Wang; Zhijun Yao; Bin Hu (Brain Structure and Function, 2022)

The selective contributions of right cerebellar lobules to reading - Hehui Li; Rebecca A. Marks; Lanfang Liu; Xiaoxia Feng; Manli Zhang; Feng Ai; Yue Gao; Mengyu Tian; Xiujie Yang; Jia Zhang; Hejing Zhong; Li Liu; et al. (Brain Structure and Function, 2022)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

BTBD9 and dopaminergic dysfunction in the pathogenesis of restless legs syndrome - Shangru Lyu; Atbin Doroodchi; Hong Xing; Yi Sheng; Mark P. DeAndrade; Youfeng Yang; Tracy L. Johnson; Stefan Clemens; Fumiaki Yokoi; Michael A. Miller; Rui Xiao; Yuqing Li (Brain Structure and Function, 2020)

Dissociating the neural correlates of the sociality and plausibility effects in simple conceptual combination - Nan Lin; Yangwen Xu; Huichao Yang; Guangyao Zhang; Meimei Zhang; Shaonan Wang; Huimin Hua; Xingshan Li (Brain Structure and Function, 2020)

Concurrent amygdalar and ventromedial prefrontal cortical responses during emotion processing: a meta-analysis of the effects of valence of emotion and passive exposure versus active regulation - Mo Yang; Shang-Jui Tsai; Chiang-Shan R. Li (Brain Structure and Function, 2020)

Reconfiguration patterns of large-scale brain networks in motor imagery - Tao Zhang; Fei Wang; Mengchen Li; Fali Li; Ying Tan; Yangsong Zhang; Hang Yang; Bharat Biswal; Dezhong Yao; Peng Xu (Brain Structure and Function, 2019)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Cannabinoid CB1 receptor signaling dichotomously modulates inhibitory and excitatory synaptic transmission in rat inner retina - Xiao-Han Wang; Yi Wu; Xiao-Fang Yang; Yanying Miao; Chuan-Qiang Zhang; Ling-Dan Dong; Xiong-Li Yang; Zhongfeng Wang (Brain Structure and Function, 2016)

SMN is required for the maintenance of embryonic stem cells and neuronal differentiation in mice - Wei-Fang Chang; Jie Xu; Chia-Chun Chang; Shang-Hsun Yang; Hsin-Yang Li; Hsiu Mei Hsieh-Li; Mong-Hsun Tsai; Shinn-Chih Wu; Winston T. K. Cheng; Ji-Long Liu; Li-Ying Sung (Brain Structure and Function, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Up-regulation of Ras/Raf/ERK1/2 signaling impairs cultured neuronal cell migration, neurogenesis, synapse formation, and dendritic spine development - Kun Yang; Fujiang Cao; Ashfaq M. Sheikh; Mazhar Malik; Guang Wen; Hongen Wei; W. Ted Brown; Xiaohong Li (Brain Structure and Function, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)